1999
DOI: 10.1016/s0022-5347(01)61987-6
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Distal Nephron Enzyme Activity After Release of Unilateral Ureteral Obstruction

Abstract: A correlation between the functional impairment of distal H+ secretion and decreased distal nephron enzyme activity has been shown. Recovery of both the functional and the enzyme activity at the distal nephron was demonstrated thirty days after obstruction release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Together, this indicates a urinary acidification defect in BUO rats after release of the obstruction, consistent with the results of previous studies (2,37,38). BUO and release of BUO were associated with downregulation of several acid-base transporters in the proximal tubule and TAL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Together, this indicates a urinary acidification defect in BUO rats after release of the obstruction, consistent with the results of previous studies (2,37,38). BUO and release of BUO were associated with downregulation of several acid-base transporters in the proximal tubule and TAL.…”
Section: Discussionsupporting
confidence: 92%
“…This finding indicates development of a urinary acidification defect after release of the obstruction, as demonstrated previ- ously (2,3,15,37,38,41). Although measurements of urinary excretion of HCO 3 Ϫ and titratable acid would provide a more complete result, the present finding is consistent with previous studies demonstrating impaired urinary acidification in the kidney after obstruction (2,3,15,37,38,41).…”
Section: Metabolic Acidosis In Buo and Urinary Acidification Defect Asupporting
confidence: 91%
See 2 more Smart Citations
“…When the distal H + pumps are intact and animals excrete highly alkaline urine, urinary pCO 2 is increased by 2-to 4-fold from arterial pCO 2 (Dubose 1982;Gonzales et al 2004;Kim et al 2004). Several earlier studies of humans and experimental animals with acute ureteral obstruction demonstrated that the difference between urine and blood pCO 2 (U-B pCO 2 ) after bicarbonate loading was much lower in the obstructed kidney than the control kidney (Walls et al 1975;Ueda 1981;Dubose and Caflisch 1985;Valles et al 1999). Therefore, it was concluded that ureteral obstruction did suppress the capacity of the CD to secrete H + and reabsorb HCO 3 -, which led to development of distal renal tubular acidosis.…”
Section: Introductionmentioning
confidence: 99%